Severe pneumonia with empyema due to multiple anaerobic infections: case report and literature review - Yu, Fangyu; Zhang, Xiaojing; Li, Yujiao; Gai, Wei; Zheng, Yafeng; Cai, Xudong (Frontiers in Medicine, 2024)
Background Cases of severe pneumonia complicated by empyema due to normal anaerobic flora from the oral cavity are infrequent. Diagnosing anaerobic infections through conventional microbiological test (CMT) is often challenging. Case presentation This study describes the case of a 67-year-old man, bedridden long-term, who developed severe pneumonia with empyema caused by multiple anaerobic bacterial infections. The patient was hospitalized with a 5-day history of cough, sputum and fever, accompanied by a 2-day history of dyspnea. Despite CMT, the specific etiology remained elusive. However, metagenomic next-generation sequencing (mNGS) identified various anaerobic bacteria in bronchoalveolar lavage fluid (BALF), blood and pleural effusion. The patient was diagnosed with a polymicrobial infection involving multiple anaerobic bacteria. Following treatment with metronidazole and moxifloxacin, the patient’s pulmonary symptoms improved. Conclusion mNGS serves as a valuable adjunctive tool for diagnosting and managing patients whose etiology remains unidentified following CMT.